Virally Mediated Connexin 26 Expression in Postnatal Scala Media Significantly and Transiently Preserves Hearing in Connexin 30 Null Mice - Zhang, Li; Wang, Wenwen; Kim, Sun Myoung; Wang, Jianjun; Zhou, Binfei; Kong, Weijia; Zheng, James; Lin, Xi (Frontiers in Cell and Developmental Biology, 2022)
Non-sensory cells in the sensory epithelium of the cochlea are connected extensively by gap junctions. Functionally null mutations in GJB6 (encoding Cx30) cause hearing loss in humans. In this study, we injected AAV1-CB7-Gjb2 into the scala media between P0-2 in the cochlea of Gjb6 knockout mice. The injection increased Cx26 expression and significantly preserved auditory functions. However, the hearing preservation gradually declined and essentially disappeared three months after the injections. In contrast, the morphological preservation was still significant at three months post-injection. We found that the expression of Cx26, at both the mRNA and protein levels, showed substantial decreases during the three-month period. Curiously, treatments by injecting AAV1-CB7-Gjb6 with the identical approach failed to yield any hearing preservation. Our results demonstrated the first successful cochlear gene therapy treatment in mouse models by virally expressing a companion gene of Gjb6.